2015
DOI: 10.17507/tpls.0505.27
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Teacher Scaffolding on Iranian Intermediate EFL Learner's Listening Comprehension Achievement

Abstract: Abstract-Among various aspects of effective instruction, scaffolding is an important concept that helps language teachers to consider the context of language learning. Teachers need to focus on strategies that are appropriate to different kinds of listening techniques and to consider the proficiency level of their students. The current investigation attempted to determine the impact of teacher scaffolding on listening comprehension of Iranian EFL learners. To this end, 60 intermediate learners (including 30 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Scaffolding has proven useful in developing students' listening skills as well. Talebinejad and Akhgar (2015) confirmed that teachers' scaffolding has a significant impact on learners' listening achievements.…”
Section: Literature Reviewmentioning
confidence: 66%
“…Scaffolding has proven useful in developing students' listening skills as well. Talebinejad and Akhgar (2015) confirmed that teachers' scaffolding has a significant impact on learners' listening achievements.…”
Section: Literature Reviewmentioning
confidence: 66%
“…According to the research done by Wallace (2014), students who learn background information have a more comprehensive understanding of the course content and participate in the class more than others. Scaffolding has proved useful in promoting learners' writing skills (Lai & Calandra, 2010) and listening ability (Talebinejad & Akhgar, 2015).…”
Section: English Immersion Programmentioning
confidence: 99%
“…Another attitudinal aspect concerns students' attitudes toward the learning environment. It is believed that language teachers' behaviors and characteristics could have an effect on students' achievement ( Nouri, 2015;Swanson, 2013;Talebinejad & Akhgar, 2015). Likewise, students' perception of the teacher could also have an effect on their achievement.…”
Section: Integrativenss and Attitudementioning
confidence: 99%